Combining ability of tropical maize germplasm in West Africa. III. Tropical maize inbreds - Kim, S.K.; Ajala, S.; Brewbaker, J.L. (2000)
One hundred elite, open-pedigree tropical and subtropical inbreds of maize (Zea mays L.) that had been screened in 60 tropical trials were evaluated as inbreds and in testcrosses in Nigeria. The 24 superior inbreds among these were chosen to create two diallel sets for evaluation of grain yield and agronomic competence. Included were lines bred in Colombia, Florida, Hawaii, India, Kenya, Nigeria, South Carolina, Texas, and Thailand. The two diallels included 78 hybrids of 13 inbreds with yellow kernels and 55 hybrids of 11 inbreds with white kernels. The diallel of 13 yellow inbreds was evaluated in 11 replicated trials throughout Nigeria, and the white diallel was evaluated similarly in five environments. About 50% of the parental inbreds had dent kernels and 50% were flints. Most dent inbreds were related to Tuxpeño and Southern U. S. Dents and most flint lines were related to Caribbean germplasm. Grain yields of the 78 yellow hybrids were obtained from ten environments, whose averages ranged from 3.0 to 7.7 t/ha. The hybrids showed highly significant differences and interacted significantly with environments. General combining ability (GCA) values for the 13 elite parents, however, did not differ significantly. Every inbred served as parent of one or more outstanding hybrids. Similarly, the 55 white hybrids differed significantly in three measured environments, whose averages ranged from 2.9 to 4.5 t/ha. GCA values for the 11 elite white parents were significant (P = 0.05), and every inbred served as parent for one or more superior hybrids interactions of hybrids with environments were highly significant for the yellow diallel, but not for the white diallel, Yellow inhreds Fla2BT106 (Florida, dent) and Ki9 and Kil4 (Thailand, flint) had the highest GCA values and superior hybrids, while the four white inbreds with superior GCA values were all bred in Nigeria (TZi3, TZi8, TZi12 and TZi15) and all were flints or flinty dents, Some outstanding hybrids were flint x dent crosses, often representing the cross of Tuxpeño and Caribbean heterotic groups, but many were not. It could be argued that each of these inbreds and their close relatives represent a potential heterotic group, drawn as they were from such a wide range of tropical germplasm, and evaluated over such a wide range of environments, Breeding tropical maize inevitably focusses on resistances to diseases, insects and stresses. These data suggest that yield heterosis is no more significant as a constraint to the tropical hybrid breeder than is inbred and hybrid tolerance of biotic and abiotic stress.